FAKTOR FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM BERALIH PROFESI MENJADI KARYAWAN ROKOK DI CV. AYUNDA - Nurmalasari, Yanti; Damayanti, Alfina; Ningsih, Kustiawati (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
The development of cigarette factories has an impact on farmers' decision-making in changing professions and decreasing the level of food production due to the small population due to industrial needs, and the relatively low ability of farmers in accessing technology, capital and institutional strength of farmers, as well as the increasing development of the cigarette industry and fierce competition today. Based on the above background, this study aims to analyze the factors that influence farmers' decisions in changing professions to non-agriculture in Jarin Village, Pademawu District, Pamekasan Regency.The location of the study was determined intentionally (purposive) based on the consideration that CV. Ayunda Permata Sejahtera, located in West Hamlet, Jarin Village, Pademawu District, Pamekasan Regency, includes a growing cigarette factory in the Jarin area, Pademawu District. The sampling method used in this study uses the slovin formula, with the number of samples to be taken as many as 31 samples from 110 populations. The data analysis used is: Logistic regression analysis so that factors that influence farmers' decision making are obtained in achieving the profession of becoming a cigarette employee at CV. Ayunda. Through this analysis, three variables were obtained that influenced a person's decision to change professions, namely job vacancies with significant data of 0.061, distance with significant data of 0.083 and economic environment with significant data of 0.048.